Altered resting-state functional connectivity of insula in children with primary nocturnal enuresis - Zhong, Shaogen; Shen, Jiayao; Wang, Mengxing; Mao, Yi; Du, Xiaoxia; Ma, Jun (Frontiers in Neuroscience, 2022)
Objective: Primary nocturnal enuresis (PNE) is a common developmental condition in school-aged children. The objective is to better understand the pathophysiology of PNE by using insula-centered resting-state functional connectivity (rsFC). Methods: We recruited 66 right-handed participants in our analysis, 33 with PNE and 33 healthy control (HC) children without enuresis matched for gender and age. Functional and structural MRI data were obtained from all children. Seed-based rsFC was used to examine differences in insular functional connectivity between PNE and HC groups. Correlation analyses were carried out to explore the relationship between abnormal insula-centered functional connectivity and clinical characteristics in the PNE group. Results: Compared with HC children, the children with PNE demonstrated decreased left and right insular rsFC with right medial superior frontal gyrus (SFG). In addition, the bilateral dorsal anterior insula (dAI) seeds also indicated the reduced rsFC with right medial SFG. Furthermore, the right posterior insula (PI) seed showed the weaker rsFC with right medial SFG, while the left PI seed displayed the weaker rsFC with the right SFG. No statistically significant correlations were to be detected between aberrant insular rsFC and clinical variables (e.g., micturition desire-awakening, bed-wetting frequency, bladder volume) in results without global signal regression (GSR) in the PNE group. However, before and after setting age as a covariate, significantly and positively correlations between bladder volume and the rsFC of the left dAI with right medial SFG, and the rsFC of the right PI with right medial SFG were found in results with GSR in the PNE group. Conclusion: To our knowledge, this study explored the rsFC patterns of the insula in children with PNE for the first time. These results uncovered the abnormal rsFC of the insula with medial prefrontal cortex without and with GSR in the PNE group, suggesting that dysconnectivity of the salience network (SN)-default mode network (DMN) may involve in the underlying pathophysiology of children with PNE. However, the inconsistent associations between bladder volume and dysconnectivity of the SN-DMN in results without and with GSR need further studies.